Preparation method of micro-nano porous copper powder and micro-nano porous copper material
Through thermal decomposition and ultrasonic and laser-assisted technologies of the carboxylate copper salt, the problems of low raw material utilization and complex process in the preparation of traditional porous copper materials are solved, and efficient and simple preparation of micro-nano porous copper powder is achieved, which improves the material Purity and sintering properties.
Patent Information
- Application Number
- CN202411477303.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2024-12-20
AI Technical Summary
The raw material utilization rate, complex process and easy introduction of impurities in the traditional porous copper material preparation method limit the further development of the material.
The copper carboxylate salt is used as the copper precursor, and the micro-nano porous copper powder is heated under the solid phase or solvent system through thermal decomposition, combining ultrasonic and laser scanning technology to improve structural uniformity and sintering performance.
It realizes efficient and simple preparation of porous copper materials, avoids smelting and corrosion processes, improves the purity and sintering performance of the materials, and reduces production costs.
Smart Images

Figure CN119159089A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal materials, and particularly relates to a preparation method of micro-nano porous copper powder and a porous copper material. Background Art
[0002] Porous copper materials have broad application prospects in the fields of thermal management, catalysts, electrode materials, adsorption materials, etc. due to their unique pore structure and excellent thermal and electrical conductivity. Traditional porous copper preparation methods mainly use dealloying methods, but these methods have some problems and limitations in practical applications, which restricts the further development of porous copper materials.
[0003] The basic principle of the dealloying method is to selectively corrode non-target elements in the alloy to form a porous structure of the remaining metal. However, the dealloying method has some significant defects in the preparation of porous copper materials. First, the dealloying method is a typical subtractive manufacturing method, which usually requires the use of high-purity alloys as raw materials. The preparation cost of high-purity alloys is high, resulting in low raw material utilization in the whole process. Secondly, the process flow of the dealloying method is relatively complicated, often involving multiple steps such as alloy smelting, corrosion, cleaning and drying, which is not only time-consuming, but also has high requirements on process control.
[0004] Therefore, it is necessary to provide a new solution to the above technical problems. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing micro-nano porous copper powder and a porous copper material, which can avoid the problems of low raw material utilization and high impurity introduction in traditional methods.
[0006] To achieve the above purpose, the technical solution provided by the present invention is as follows:
[0007] In a first aspect, the present invention provides a method for preparing micro-nano porous copper powder, which comprises: providing a copper precursor, wherein the copper precursor is a copper carboxylate salt; heating the copper precursor in a solid phase system or a solvent system to thermally decompose the copper precursor to form the micro-nano porous copper powder.
[0008] In one or more embodiments, the copper precursor includes at least one of monocarboxylic acid copper such as copper formate, dicarboxylic acid copper such as copper oxalate, tricarboxylic acid copper such as copper citrate, tetracarboxylic acid such as copper pyromellitic acid, and derivatives thereof containing C, H, O elements or combination substituents.
[0009] In one or more embodiments, the heating temperature of the copper precursor is 100-400°C.
[0010] In one or more embodiments, the preparation method specifically includes: spreading a copper precursor in a container; placing the container in a reaction furnace, introducing a protective gas, and heating the copper precursor at a temperature of 100 to 400° C. for 30 to 90 minutes to thermally decompose the copper precursor to form micro-nano porous copper powder.
[0011] In one or more embodiments, the preparation method specifically includes: placing a copper precursor in a container, adding a solvent to disperse the copper precursor; placing the container in a reaction furnace, passing a protective gas, heating and refluxing the copper precursor solution at a temperature of 100 to 400° C. for 30 to 90 minutes, so that the copper precursor is thermally decomposed to form micro-nano porous copper powder.
[0012] In one or more embodiments, during the heating of the copper precursor, the copper precursor is dispersed by ultrasonic wave.
[0013] In one or more embodiments, the frequency of the ultrasonic wave is 20-60 kHz, and the power is 50-800W.
[0014] In one or more embodiments, during the heating of the copper precursor, the copper precursor is irradiated by laser scanning.
[0015] In one or more embodiments, the wavelength of the laser is 400-1100 nm, the power is 1-10 W, and the scanning frequency is 4-6 Hz.
[0016] In a second aspect, the present invention provides a porous copper material, which includes the micro-nano porous copper powder prepared by the preparation method of the micro-nano porous copper powder as described above.
[0017] Compared with the prior art, the preparation method of the micro-nano porous copper powder and the porous copper material provided by the present invention prepare the micro-nano porous copper powder by thermal decomposition of a copper precursor to achieve an efficient and simple preparation process; copper carboxylate is selected as a precursor, and under appropriate heating conditions, it is directly thermally decomposed to form a micro-nano porous copper powder with a nano or submicron pore structure, thereby avoiding the complicated smelting, corrosion process and impurity introduction in the traditional dealloying method. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0019] Figure 1 This is a flow chart of a method for preparing micro-nano porous copper powder in one embodiment of the present invention;
[0020] Figure 2 This is a microscopic morphology of the micro-nano porous copper powder prepared in Example 1 of the present invention;
[0021] Figure 3 This is a microscopic morphology of the micro-nano porous copper powder prepared in Example 2 of the present invention;
[0022] Figure 4 This is a microscopic morphology of the micro-nano porous copper powder prepared in Example 3 of the present invention;
[0023] Figure 5 This is a microscopic morphology of the micro-nano porous copper powder prepared in Example 4 of the present invention;
[0024] Figure 6 This is a microscopic morphology of the bulk porous copper material after sintering the micro-nano porous copper powder prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0025] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0026] It should be noted that, unless otherwise indicated, all numbers used in the specification and claims to represent feature sizes, quantities and physical properties should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters listed in the above specification and the attached claims are approximate values, and those skilled in the art can use the teachings disclosed herein to seek to obtain the desired properties and appropriately change these approximate values. The use of numerical ranges expressed as endpoints includes all numbers within the range and any range within the range, for example, 1 to 5 includes 1, 1.2, 1.4, 1.55, 2, 2.75, 3, 3.80, 4 and 5, etc.
[0027] Porous copper materials are widely used in thermal management, electrode materials, catalysts and adsorbents due to their good thermal conductivity, electrical conductivity and high specific surface area. Common preparation methods mainly include dealloying. The dealloying method forms a porous structure by removing non-target elements in the alloy through corrosion. However, this method has a complex process flow and involves multiple corrosion and cleaning processes. In addition, the high-purity alloy raw materials required are expensive and the raw material utilization rate is low, which limits the economy and feasibility of large-scale industrial production.
[0028] In view of the above technical problems, the core technology of the present invention is to prepare micro-nano porous copper powder by thermal decomposition of copper precursors to achieve an efficient and simple preparation process. Specifically, the present invention selects carboxylic acid copper salts (such as copper formate, copper oxalate, copper citrate, copper pyromellitic acid, etc.) as precursors, and directly thermally decomposes them under appropriate heating conditions to form micro-nano porous copper powder with nano or submicron pore structure. This method avoids the complicated smelting and corrosion process in the traditional dealloying method, and effectively avoids the introduction of impurities.
[0029] In addition, in order to further improve the structural uniformity and sintering performance of micro-nano porous copper powder, the present invention also combines ultrasonic-assisted and photothermal effect technologies. The vibration effect of ultrasound allows the precursor to be continuously dispersed during the reaction to avoid particle aggregation. At the same time, lasers are used to apply photothermal effects to the precursor to accelerate local decomposition of the material and promote the formation of a pore structure.
[0030] Please refer to Figure 1 FIG. 1 is a flow chart of a method for preparing micro-nano porous copper powder according to an embodiment of the present invention. The method for preparing micro-nano porous copper powder specifically comprises the following steps:
[0031] S101: providing a copper precursor, wherein the copper precursor is a copper carboxylate salt.
[0032] It should be noted that the copper precursor is copper carboxylate, and this choice helps to achieve efficient and pure porous copper material preparation. Copper carboxylate is a class of copper organic compounds, which contains copper ions and organic acid radicals (such as formate, oxalate, citrate or pyromellitic acid). These copper salts are easy to decompose, the pyrolysis process is simple, and the decomposition products are mainly copper, carbon dioxide and water, and no complex by-products are produced.
[0033] In the specific implementation process, the copper precursor can be obtained in a variety of ways. For example, copper formate can be prepared by dissolving copper hydroxide in formic acid; copper oxalate can be generated by the reaction of oxalic acid and copper salts. These preparation methods are relatively simple, and the precursors are easy to purify, which can ensure high-quality initial materials. According to actual needs, the precursor can be in powder or solution state. If used in powder form, the material can be directly subjected to solid phase pyrolysis; if used in solution form, the dispersibility of the precursor can be further improved, which is conducive to the formation of a uniform porous structure.
[0034] The main purpose of choosing copper carboxylates as precursors is to take advantage of their superior thermal decomposition properties. Copper carboxylates are easily decomposed into copper and other simple volatile products under heating conditions, without the need for additional reducing agents or catalysts, avoiding the introduction of impurities and ensuring the purity of the final micro-nano porous copper powder. This feature helps to obtain high-quality porous copper materials and simplifies subsequent processing. In addition, the selection of different copper carboxylates can also control the microstructure of porous copper by adjusting the decomposition temperature and decomposition rate. For example, copper formate has a low decomposition temperature and is suitable for the preparation of porous materials under mild conditions; copper citrate has a higher decomposition temperature and can be used in processes that require higher temperatures to promote reactions.
[0035] Preferably, the copper precursor includes at least one of monocarboxylic acid copper such as copper formate, dicarboxylic acid copper such as copper oxalate, tricarboxylic acid copper such as copper citrate, tetracarboxylic acid such as copper pyromellitic acid, and derivatives thereof containing C, H, O elements or combination substituents.
[0036] The decomposition temperature of copper formate is relatively low (usually below 200°C), which is suitable for preparing micro-nano porous copper powder under mild conditions. It can be used in temperature-sensitive occasions or for preparing materials with fine pore structures. The decomposition temperature of copper citrate is slightly higher, generally between 200°C and 300°C, which is suitable for conventional pyrolysis processes and can obtain uniform nano- or submicron-sized porous structures. The decomposition temperature of copper pyrophthalate is higher, close to 300°C to 400°C, which makes it more suitable for preparing more complex or directional pore structures under conditions requiring higher temperatures and energy input. In addition, copper citrate has a multi-carboxyl structure in its molecules, which helps to form larger pores or multi-level pore structures.
[0037] S102: In a solid phase system or a solvent system, heating the copper precursor to thermally decompose the copper precursor to form micro-nano porous copper powder.
[0038] In step S102, copper carboxylate salts (such as copper formate, copper oxalate, copper citrate or copper pyromellitic acid) are decomposed by heat energy to generate metallic copper and other volatile products (such as carbon dioxide and water), thereby forming copper powder with a porous structure.
[0039] In a solid phase system, the copper precursor is usually evenly spread in a container in the form of powder for heat treatment. The container can be placed in a protective atmosphere (such as nitrogen or argon) to avoid oxidation of copper. The heating temperature of solid phase pyrolysis is usually between 100 and 400 ° C, depending on the properties of the precursor. For example, the decomposition temperature of copper formate is relatively low and is suitable for operation below 200 ° C, while the decomposition temperatures of copper oxalate, copper citrate, and copper pyromellitic acid are relatively high and can be carried out between 200 and 400 ° C, respectively. Thermal decomposition under this system can be completed quickly and efficiently, without the need for solvent treatment, and is suitable for large-scale production. Since there is no liquid phase involved, the resulting micro-nano porous copper powder has high purity and is not affected by solvent residues.
[0040] In a solvent system, the copper precursor is dissolved in a solvent (such as ethylene glycol, carbitol, etc.), and then heated to the boiling point of the solvent or a higher temperature, so that the solvent gradually evaporates, and the copper precursor decomposes into micro-nano porous copper powder. The advantage of the solvent system is that the evaporation of the solvent can take away part of the reaction heat, which helps to control the reaction temperature and decomposition rate. In addition, the solvent helps to evenly disperse the precursor, which is conducive to forming a more uniform pore structure. Therefore, for applications that require highly uniform microstructures (such as catalyst supports), thermal decomposition of solvent systems is more suitable.
[0041] The heating temperature of the copper precursor is preferably 100-400°C. Too low a temperature will lead to incomplete decomposition and insufficient porosity of the material; while too high a temperature may cause particle sintering, resulting in collapse of the pore structure.
[0042] In an exemplary embodiment, a copper precursor is spread flat in a container; the container is placed in a reaction furnace, a protective gas is introduced, and the copper precursor is heated at a temperature of 100 to 400° C. for 30 to 90 minutes to thermally decompose the copper precursor to form micro-nano porous copper powder.
[0043] Spreading the copper precursor flat in the container can ensure that the precursor is evenly heated during the thermal decomposition process, avoiding local overheating or insufficient decomposition due to accumulation. Evenly distributed copper precursor helps to form a more uniform pore structure, ensuring the consistency of the pore size and specific surface area of the micro-nano porous copper powder on a microscopic scale.
[0044] The container is placed in a reactor and a protective gas is introduced. The purpose of this step is to prevent copper oxidation during the heating process. Protective gases such as nitrogen or argon can form an inert environment in the reaction zone, isolate oxygen from contact, and maintain the purity of copper. For porous metal materials, the improvement of purity directly affects their conductivity, catalytic activity and other physical and chemical properties. Therefore, the use of a protective atmosphere is an important guarantee for the preparation of micro-nano porous copper powder by thermal decomposition.
[0045] In an exemplary embodiment, a copper precursor is placed in a container, and a solvent is added to disperse the copper precursor to form a copper precursor solution; the container is placed in a reaction furnace, a protective gas is introduced, and the copper precursor solution is heated and refluxed at a temperature of 100 to 400° C. for 30 to 90 minutes to thermally decompose the copper precursor to form micro-nano porous copper powder.
[0046] A copper precursor (such as copper formate, copper oxalate, copper citrate or copper pyromellitic acid) is added to a container, and a solvent is added to completely disperse it. The purpose of this step is to form a uniform copper precursor solution. The solvent can be carbitol, which has good dispersibility and a high boiling point and is suitable for high-temperature treatment under reflux conditions. Through the dispersion treatment, it can be ensured that the precursor is evenly distributed in the solvent, which helps the uniform heating and decomposition reaction in the subsequent thermal decomposition process.
[0047] In an exemplary embodiment, during the heating of the copper precursor, the copper precursor is dispersed by ultrasonic waves, wherein the frequency of the ultrasonic waves is preferably 20 to 60 kHz, and the power is preferably 50 to 800 W.
[0048] In the preparation process of micro-nano porous copper powder, the copper precursor is dispersed by ultrasound in order to improve the uniformity and reaction efficiency of the material during the thermal decomposition process. Ultrasonic dispersion uses the mechanical vibration of sound waves to continuously impact the copper precursor in the solution with energy, thereby avoiding the agglomeration of particles and promoting the uniform dispersion of the precursor. This process can improve the formation quality of the porous structure and help optimize the microscopic properties of the material.
[0049] In a specific implementation, ultrasonic dispersion can be carried out simultaneously with the heating process, and an ultrasonic device with a frequency between 20 and 60 kHz and a power between 50 and 800 W can be used. The vibration effect of the ultrasonic wave produces a strong cavitation effect in the reaction medium, that is, a tiny explosion is formed in the medium. This effect will cause local high temperature and high pressure changes, enhance the convection and mass transfer effects in the medium, and thus improve the dispersibility and decomposition rate of the copper precursor.
[0050] In an exemplary embodiment, during the heating of the copper precursor, the copper precursor is irradiated by laser scanning, wherein the wavelength of the laser is preferably 400 to 1100 nm, the power is preferably 1 to 10 W, and the scanning frequency is preferably 4 to 6 Hz.
[0051] Laser irradiation directly acts on the precursor through a light source of a specific wavelength, producing a local high temperature effect, thereby accelerating the decomposition process and optimizing the formation of the pore structure.
[0052] Laser irradiation can be carried out simultaneously with the heating process, and precise control of the decomposition of the precursor can be achieved by selecting the appropriate wavelength and power. For example, in the decomposition process of copper formate or copper oxalate, the use of a laser with a wavelength of 532nm (corresponding to green laser) can effectively absorb the energy of the material, produce a photothermal effect, and rapidly increase the local temperature, thereby accelerating the thermal decomposition rate. At the same time, the power setting between 1 and 10W can prevent particle sintering or pore structure collapse caused by excessive heating. For materials that decompose at higher temperatures, such as copper pyrophthalate, selecting a laser with a wavelength of 1064nm (near-infrared light) can help with deeper heating and energy transfer to ensure thorough decomposition.
[0053] The present invention also provides a porous copper material, which includes the micro-nano porous copper powder prepared by the above-mentioned preparation method of the micro-nano porous copper powder.
[0054] The present invention will be further described below in conjunction with specific embodiments and comparative examples.
[0055] Example 1
[0056] Weigh 200 grams of copper formate, spread it flat in a 20cm×30cm×3cm stainless steel plate, place it in a transmission mesh belt furnace, use nitrogen as the protective gas, and set the temperature in the high temperature zone to 200°C; after heating in the mesh belt furnace for 60 minutes and cooling for 60 minutes, micro-nano porous copper powder is obtained.
[0057] Figure 2 The microscopic morphology of the micro-nano porous copper powder prepared in Example 1 is about 30 μm in particle size, 400-800 nm in ligament length, 200-400 nm in ligament width, 200-600 nm in pore size, and 1.89 m in specific surface area. 2 / g.
[0058] Example 2
[0059] Weigh 200 grams of copper formate, spread it flat in a 20 cm × 30 cm × 3 cm stainless steel plate, place it in a transmission mesh belt furnace, use nitrogen as the protective gas, and set the temperature in the high temperature zone to 200 ° C; heat it in the mesh belt furnace for 60 minutes, use an ultrasonic device (frequency 40 kHz, power 200 W) to ultrasonically disperse the copper formate during the heating process, and then cool it for 60 minutes to obtain micro-nano porous copper powder.
[0060] Figure 3 The microscopic morphology of the micro-nano porous copper powder prepared in Example 2 is about 20 μm in particle size, 200-600 nm in ligament length, 200-300 nm in ligament width, 200-400 nm in pore size, and 2.15 m in specific surface area.2 / g.
[0061] Example 3
[0062] Weigh 200 grams of copper formate, spread it in a 20 cm × 30 cm × 3 cm stainless steel plate, place it in a transmission mesh belt furnace, use nitrogen as a protective gas, and set the temperature in the high temperature zone to 200 ° C; heat it in the mesh belt furnace for 60 minutes, and use a laser light source (wavelength 532nm, power 5W, scanning frequency 5Hz) to scan and irradiate the copper formate during the heating process, and then cool it for 60 minutes to obtain micro-nano porous copper powder.
[0063] Figure 4 The microscopic morphology of the micro-nano porous copper powder prepared in Example 3 is about 25 μm in particle size, 300-1200 nm in ligament length, 200-600 nm in ligament width, 200-800 nm in pore size, and 2.02 m in specific surface area. 2 / g.
[0064] Example 4
[0065] 200 g of copper formate was weighed, spread on a 20 cm × 30 cm × 3 cm stainless steel plate, placed in a transmission mesh belt furnace, nitrogen was used as a protective gas, and the temperature in the high temperature zone was set to 200 ° C; heated in the mesh belt furnace for 60 min, and during the heating process, an ultrasonic device (frequency 40 kHz, power 200 W) was used to ultrasonically disperse the copper formate, and a laser light source (wavelength 532 nm, power 5 W, scanning frequency 5 Hz) was used to scan and irradiate the copper formate, and then cooled for 60 min to obtain a micro-nano porous copper powder.
[0066] Figure 5 The microscopic morphology of the micro-nano porous copper powder prepared in Example 4 is about 25 μm in particle size, 200-400 nm in ligament length, 100-300 nm in ligament width, 50-300 nm in pore size, and 2.32 m in specific surface area. 2 / g.
[0067] Sintering performance test
[0068] Weigh 30 grams of each of the micro-nano porous copper powders prepared in Examples 1 to 4, respectively, and load them into the same mold, compact the copper powder under the same conditions, and then put the mold into a reaction furnace, sinter at 800°C for 60 minutes to obtain a bulk porous copper material. The bulk porous copper material obtained by sintering the micro-nano porous copper powder in each embodiment was tested for performance, and the sintering performance of the micro-nano porous copper powder prepared in each embodiment was obtained. The test results are shown in the following table:
[0069] Source of Micro-Nano Porous Copper Powder Strength (MPa) Water absorption rate against gravity s / cm Example 1 35.82 2.8 Example 2 37.15 3 Example 3 38.66 2.5 Example 4 45.27 1.8
[0070] It can be seen from the above table that the sintered body strength of the micro-nano porous copper powder prepared in Example 2 and Example 3 is slightly improved compared with the micro-nano porous copper powder prepared in Example 1.
[0071] This is because ultrasonic dispersion induces cavitation effect (i.e., formation of tiny explosions) through the vibration of sound waves in the medium, thereby generating local high temperature and high pressure. This effect can enhance the convection and mass transfer efficiency of the medium and promote the uniform dispersion of copper precursor particles. The uniformly dispersed precursor will form a more regular pore structure during the pyrolysis process, and the average particle size of the particles will be reduced, which will help to increase the contact area of the particles and the formation of sintering necks during sintering, thereby slightly improving the sintering performance. The vibration of ultrasound can also increase the activity of the particle surface. For example, through ultrasonic treatment, microscopic defects or roughness may be produced on the surface of the particles. These surface features can enhance the mechanical bonding force and diffusion rate between particles during the sintering process.
[0072] Laser scanning heating generates high energy in local areas through the photothermal effect, allowing the copper precursor to quickly reach the decomposition temperature. This local heating can accelerate the decomposition rate of the precursor and form a uniform pore structure and fine porous characteristics. This uniform microstructure helps to rearrange particles during sintering and improve the densification effect. Laser scanning can also adjust the surface properties of the material, such as increasing the surface roughness or introducing local micro stress. These characteristics help to promote the formation of sintering necks and increase the diffusion rate during the sintering process.
[0073] It can be seen from the above table that the micro-nano porous copper powder prepared in Example 4 has a significantly improved sintered body strength compared to the micro-nano porous copper powder prepared in Example 1.
[0074] This is because ultrasonic dispersion combined with laser scanning can synergistically improve the dispersion state, surface activity, microstructure uniformity and stress distribution of particles, thereby improving the particle characteristics from the aspects of physical vibration and thermal energy, respectively.
[0075] The dispersive effect of ultrasound can ensure a more uniform laser heating effect, thereby forming a regular pore structure and consistent particle distribution during the pyrolysis process. Compared with ultrasonic dispersion or laser scanning alone, this synergistic effect helps to increase the contact area between particles and densification during sintering, and reduce structural defects. The surface roughness and defects generated by ultrasound can be further activated by laser heating, significantly enhancing the surface diffusion between particles and the sintering driving force.
[0076] Ultrasonic dispersion ensures uniform distribution of particles at the macro level, and laser scanning further optimizes the particle surface and internal structure at the micro level. The combination of the two makes the particles highly dispersible and highly surface active, greatly promoting atomic diffusion and bonding during the sintering process.
[0077] Porous copper sintered materials have good thermal conductivity and are widely used as core components of heat pipes, temperature equalizers and other heat dissipation devices. The irregular copper powder widely used in the industry has too small pore sizes after sintering, resulting in large resistance to the return of liquid working fluids, and too small pore sizes lead to insufficient capillary force. The two hinder each other, and it is impossible to achieve a fast water absorption rate through simple copper powder sintering. The porous copper material obtained by sintering the micro-nano porous copper powder of the present invention has the characteristics of coexistence of ultra-large micron-sized pores between powders and submicron pores within a single powder. The synergistic effect of the permeability and capillary force advantages enables the material to exhibit the performance of rapid water absorption in a reverse gravity environment. The micro-nano porous copper powder prepared in Example 4 has a better void size (such as Figure 6 The performance is particularly evident.
[0078] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0079] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method for preparing micro-nano porous copper powder, characterized in that: include: Providing a copper precursor, wherein the copper precursor is a copper carboxylate salt; The copper precursor is heated in a solid phase system or a solvent system to thermally decompose the copper precursor to form micro-nano porous copper powder.
2. The method for preparing porous copper powder according to claim 1, characterized in that: The copper precursor includes at least one of monocarboxylic acid copper, dicarboxylic acid copper, tricarboxylic acid copper and tetracarboxylic acid.
3. The method for preparing micro-nano porous copper powder according to claim 1, characterized in that: The heating temperature of the copper precursor is 100-400°C.
4. The method for preparing micro-nano porous copper powder according to claim 1, characterized in that: The preparation method specifically comprises: Spread the copper precursor evenly in the container; The container is placed in a reaction furnace, a protective gas is introduced, and the copper precursor is heated at a temperature of 100 to 400° C. for 30 to 90 minutes to thermally decompose the copper precursor to form micro-nano porous copper powder.
5. The method for preparing micro-nano porous copper powder according to claim 1, characterized in that: The preparation method specifically comprises: placing a copper precursor in a container, and adding a solvent to disperse the copper precursor to form a copper precursor solution; The container is heated, a protective gas is introduced, and the copper precursor solution is heated and refluxed at a temperature of 100 to 400° C. for 30 to 90 minutes to thermally decompose the copper precursor to form micro-nano porous copper powder.
6. The method for preparing micro-nano porous copper powder according to claim 1, characterized in that: During the heating of the copper precursor, the copper precursor is dispersed by ultrasonic wave.
7. The method for preparing micro-nano porous copper powder according to claim 6, characterized in that: The frequency of the ultrasonic wave is 20-60kHz, and the power is 50-800W.
8. The method for preparing micro-nano porous copper powder according to any one of claims 1 to 7, characterized in that: During the heating of the copper precursor, the copper precursor is irradiated by laser scanning.
9. The method for preparing micro-nano porous copper powder according to claim 8, characterized in that: The wavelength of the laser is 400-1100nm, the power is 1-10W, and the scanning frequency is 4-6Hz.
10. A porous copper material, characterized in that: The invention comprises the micro-nano porous copper powder prepared by the preparation method of the micro-nano porous copper powder as described in any one of claims 1 to 9.
Citation Information
Cited By
Preparation method of high-uniformity ultra-dispersion nano hollow hydrangea copper powder
CN120533112A
